High-dose chemotherapy followed by autologous stem cell transplantation for adult patients With first relapse of Ewing's sarcoma: A single institution experience. Issue 49 (9th December 2022) - Paksoy, Nail; Ferhatoglu, Ferhat; Dogan, İzzet and Khanmammadov, Nijat and Iribas Celik, Ayca and Gulbas, Zafer and Başaran, Mert
Abstract : The prognosis of patients with Ewing's sarcoma family of tumors (ESFT) relapse is poor; the 5-year overall survival (OS) is 13%. We evaluated the effectivity of high-dose therapy (HDT) with autologous stem cell transplantation (ASCT) in adult patients with ESFT relapse. Between January 2010 and January 2021, we retrospectively analyzed 20 patients with ESFT who received HDT upon relapse. A combination of busulfan with melphalan was used as a conditioning regimen before ASCT. The median follow-up from diagnosis and from first relapse was 46.08 months (range; 10.71–186.87) and 14.41 months (range; 4.34–104.11), respectively. The median of age patients was 21.2 years (range, 17.6–25.3), and 10 (50%) patients were female. The tumor originated from the bone in 13 patients and soft tissue in 7 patients. Twelve patients had early (<2 years) relapse, and 8 patients had late (>2 years) relapse. Before HDT, 13 (65%) and 7 (35%) patients had pulmonary and extrapulmonary metastasis, respectively. After induction chemotherapy, 14 patients achieved complete response. The median OS1 and OS2 were 51.6 months (95% confidence interval [CI], range: 16.2–87) and 15.7 months (95% CI, range: 10.2–21.2), respectively. The 1-, 2-, and 5-year OS rates were 50%, 30%, and 15%, respectively. One patient died (sepsis) 1 month after ASCT. In univariate analyses, a disease-free interval (DFI) of < 2 years ( P = .008) and incomplete response ( P = .021) before ASCT were poor prognostic factors for OS2.HDT with ASCT can result in long-term survival of patients with ESFT relapse. HDT should be considered an important treatment opt ion in patients with a DFI > 2 years and complete response before transplantation.